2024
DOI: 10.1111/srt.13642
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of case series and clinical trials investigating systemic oral or injectable therapies for the treatment of vitiligo

Alireza Jafarzadeh,
Arash Pour Mohammad,
Mina Khosravi
et al.

Abstract: Aims and objectivesThe purpose of this study is to investigate the effectiveness and safety of oral and injectable systemic treatments, such as methotrexate, azathioprine, cyclosporine, tofacitinib, baricitinib, corticosteroids, statins, zinc, apremilast, etc., for treating vitiligo lesions.MethodDatabases including PubMed, Scopus, and Web of Science were meticulously searched for studies spanning from 2010 to August 2023, focusing on systemic oral and injectable therapies for vitiligo, using comprehensive key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…systematically reviewed various studies of oral or injectable treatments for vitiligo and showed that different doses of OMP therapy produced significantly effective results. 21 However the specific drugs used for OMP therapy are different in different literature and our study provides new insights into the addition of methylprednisolone to OMP therapy. In addition, they found that Methotrexate, Azathioprine, Cyclosporine, Mycophenolate mofetil, Simvastatin, Apremilast, Minocycline, Afamelanotide, Tofacitinib, Baricitinib, Antioxidants, and oral and injectable forms of CSs are all effective in the treatment of vitiligo, so future research directions should favor a comparison of the safety and efficacy of TGP in combination with these drugs.…”
Section: Discussionmentioning
confidence: 90%
“…systematically reviewed various studies of oral or injectable treatments for vitiligo and showed that different doses of OMP therapy produced significantly effective results. 21 However the specific drugs used for OMP therapy are different in different literature and our study provides new insights into the addition of methylprednisolone to OMP therapy. In addition, they found that Methotrexate, Azathioprine, Cyclosporine, Mycophenolate mofetil, Simvastatin, Apremilast, Minocycline, Afamelanotide, Tofacitinib, Baricitinib, Antioxidants, and oral and injectable forms of CSs are all effective in the treatment of vitiligo, so future research directions should favor a comparison of the safety and efficacy of TGP in combination with these drugs.…”
Section: Discussionmentioning
confidence: 90%
“…These treatments have been extensively investigated for a wide range of skin diseases, which can be categorized into two main groups: primary skin diseases, including androgenetic alopecia [ 6 , 7 ], vitiligo [ 8 , 9 ], alopecia areata [ 10 ], telogen effluvium [ 11 ], melasma [ 12 ], acne vulgaris [ 13 ], lichen sclerosus et atrophicus (LSA) [ 14 ], erosive oral lichen planus [ 15 , 16 ], and dystrophic epidermolysis bullosa [ 17 ]; and skin conditions secondary to damage such as acne scars, hypertrophic scars from burns, erosions, and ulcers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%